A low‐profile compact UWB antenna array for sub‐6 GHz MIMO applications in 5G metal‐frame smartphones. Issue 10 (20th July 2022) - Fakharian, Mohammad M.
Abstract: In this article, a low‐profile compact ultra wideband (UWB) multiple input multiple output (MIMO) array antenna system for the application in sub‐6 GHz fifth‐generation (5G) metal‐frame smartphones is introduced. Each element of the array antenna system consists of an E‐shaped monopole antenna element that feeding by a microstrip line, a thin rectangular‐shaped slot in the ground plane and multiple slots and slits in the metal frame. Each element has a compact structure and only occupies an area of 11.4 × 8.4 mm 2 (0.125 λ0 × 0.092 λ0, λ0 is the wavelength of free‐space at 3.3 GHz) with a height of 6 mm for the metal frame. The MIMO system can work in the 3.3–6 GHz band (| S 11 | < −6 dB) that is UWB for the future 5G mobile terminals. A prototype of the MIMO antenna system is fabricated and tested. The proposed MIMO antenna offers good return loss, transmission coefficient (over 12.8 dB), sufficient radiation efficiencies (over 50%), envelope correlation coefficient (below 0.06) and ergodic channel capacity (between 35 and 40 bps/Hz) across the working band, although it is printed on a high‐loss FR‐4 substrate. Moreover, the MIMO array system can preserve suitable operation in the presence of human hand, large display panel and battery. The MIMO antenna provides good features for use in the 5G communications.